2017
DOI: 10.1002/rmb2.12070
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony of the first division as an index of the blastocyst formation rate during embryonic development

Abstract: PurposeTo devise an uninvasive selection system for human embryos with high developmental potential after a single oocyte retrieval cycle by comparing the in vitro and in vivo effectiveness of first division synchrony against subsequent embryonic developmental stages.MethodsThe effects of using assisted reproductive technology on 948 embryos that were produced in 137 cycles were examined by dividing the embryos into “early cleavage” (first division within 25.90 hours) and “late cleavage” (first division at or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In our study, t2 (first cleavage), ECC1 (duration of the cell cycle) and t4 (third cleavage) occurred significantly earlier in the ASCC group compared to the NSCC group. Published data indicate that a precocious first cleavage (t2 < 25.9 h) is predictive of blastulation [33,34], embryonic quality on day 3 post-fertilization [35] and a better implantation rate [25,33]. The t4 seems to be associated with the formation of a good-quality blastocyst [33] and a better implantation rate [19,25,33] in favor of early onset.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, t2 (first cleavage), ECC1 (duration of the cell cycle) and t4 (third cleavage) occurred significantly earlier in the ASCC group compared to the NSCC group. Published data indicate that a precocious first cleavage (t2 < 25.9 h) is predictive of blastulation [33,34], embryonic quality on day 3 post-fertilization [35] and a better implantation rate [25,33]. The t4 seems to be associated with the formation of a good-quality blastocyst [33] and a better implantation rate [19,25,33] in favor of early onset.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is a delay in the time to 2 cells (t2), the other possibility is that t2 is normal, but the duration of the second cell cycle (cc2) was prolonged. In the rst case, early cleavage has become an established developmental competence biomarker in standard morphology selection schemes [24].The timing and synchronicity of the rst division are useful assessments for determining blastocyst formation rate [25,26]. Observation via time-lapse imaging (TLI) has revealed lower implantation and live birth potential for embryos that undergo cleavage after 30 hours (t2>30hrs).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, using time-lapse monitoring, the latest incidence of first cleavage was recorded at 39 hpi, but blastocysts did not develop from embryos that cleaved later than 27 hpi. In humans, two-cell embryos that cleave at 25–28 hpi are usually selected for transfer to improve the chance of achieving pregnancy [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a large synchronization of the first division for early embryos (22–23 hpi) and the majority of the best quality embryos cleaved at 22(±39 min) hpi. In humans, it was found that the blastocyst formation rate was significantly increased in the high-synchrony (first division synchrony ±3.96 h) compared with the low-synchrony groups (first division synchrony longer than 3.96 h) [ 31 ]. Further cell divisions were not synchronous and embryos dividing t2–t3 at 8–15 h after the first cleavage had the highest development rates [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation